Penggunaan Aplikasi Perpustakaan Digital (Ipusnas) Sebagai Sumber Referensi Bagi Mahasiswa Semester Akhir Program Studi Perpustakaan Dan Sains Informasi Universitas Sari Mutiara Indonesia - Zakiah, Diana Maulida; Fithria Rizka Sirait; Maltus Hutagalung; Febryna Priti Sirait (Universitas Sari Mutiara Indonesia, 2024)
This study aims to analyze how the use of the iPusnas application as a reference source for final students of the Library and Information Science Study Program, Sari Mutiara University, Indonesia. The research method used is qualitative, with observation data collection techniques, interviews, and literature studies. The informants are 10 people. The results of the study show that the use of the iPusnas application as a reference source for final students is quite optimal and can meet the information needs of its users with features that facilitate and the availability of quite diverse collections about various scientific fields.